Protein nutritional supplement with bacuri almonds (Attalea phalerata Mart. Ex Spreng) for vegetarian sports: development, characterization, and shelf life - CUNHA, Flávio; MIAGUSKU, Luciana; MACEDO, Maria Lígia Rodrigues; HIANE, Priscila Aiko; SANCHES, Fabiane La Flor Ziegler (Food Science and Technology, 2024)
The aim of the study was to develop and evaluate a protein nutritional supplement formulated with bacuri almonds (Attalea phalerata Mart. Ex Spreng) for vegetarian athletes. The almonds were processed to prepare defatted flour, from which a protein concentrate was obtained through aqueous extraction and lyophilization. The protein concentrate was used to formulate two protein supplement formulations. The nutritional, compositional, and amino acid profiles of the freeze-dried bacuri almond flour and the supplement formulations were characterized. The shelf life of the supplement was evaluated, and its microbiological and sensory composition was analyzed. The results showed that bacuri almonds are a promising source of plant-based protein, and the supplement developed in this study met the nutritional needs of vegetarian athletes. Two final supplement formulations were obtained: one consisting of 70% bacuri almond flour with a protein content of 43%, and the other a protein blend consisting of 40% bacuri almonds and 40% commercial supplement based on rice and peas with a protein content of 47%. Despite some loss of amino acids during the optimization of protein concentration, the supplement formulations had satisfactory microbiological and sensory composition during the 28-day shelf-life test. These findings provide an alternative protein supplement option for athletes and individuals with a vegetarian diet.